LEGAL PLURALISM IN SUBAK REGULATION IN BALI - I Putu Sastra Wibawa (Unmas Press, 2019)
Subak as a part of Balinese culture is a social organization that has the potential to improve the welfare of the community through its main activities in regulating the use of water for irrigation of rice fields, so it needs to be recognized and respected its existence along with its traditional rights. To maintain the existence of Subak, the Government Provincial of Bali through its authority in the era of autonomy to form a local regulation that specificially regulates the Subak, which is contained in local regulations Number 9 of 2012. Interesting to be studied Subak as an institution based on Pancasila, Indonesian Constitution, concept of tri hita karana, and imbued Hindusm. Then, in term of legal theory, Subak arrangement pertained in the implementation of legal pluralism theory into the local regulations in Bali, Thus the study needs to be done, 1) What is principles of legal pluralism contained in the local regulations on Subak, and 2) Why local regulations on Subak need to be framed in the politics of legal pluralism. The theory used to dissect the theory of legal pluralism and the theory of recht state, using normative research methods, with the statute, conceptual, analytical, and philosophy approach.